1 ; RUN: opt < %s -reassociate -S | FileCheck %s 2 3 ; Check that a*a*b+a*a*c is turned into a*(a*(b+c)). 4 5 define float @fmultistep1(float %a, float %b, float %c) { 6 ; CHECK-LABEL: @fmultistep1( 7 ; CHECK-NEXT: [[REASS_ADD1:%.*]] = fadd fast float %c, %b 8 ; CHECK-NEXT: [[REASS_MUL2:%.*]] = fmul fast float %a, %a 9 ; CHECK-NEXT: [[REASS_MUL:%.*]] = fmul fast float [[REASS_MUL:%.*]]2, [[REASS_ADD1]] 10 ; CHECK-NEXT: ret float [[REASS_MUL]] 11 ; 12 %t0 = fmul fast float %a, %b 13 %t1 = fmul fast float %a, %t0 ; a*(a*b) 14 %t2 = fmul fast float %a, %c 15 %t3 = fmul fast float %a, %t2 ; a*(a*c) 16 %t4 = fadd fast float %t1, %t3 17 ret float %t4 18 } 19 20 ; Check that a*b+a*c+d is turned into a*(b+c)+d. 21 22 define float @fmultistep2(float %a, float %b, float %c, float %d) { 23 ; CHECK-LABEL: @fmultistep2( 24 ; CHECK-NEXT: [[REASS_ADD:%.*]] = fadd fast float %c, %b 25 ; CHECK-NEXT: [[REASS_MUL:%.*]] = fmul fast float [[REASS_ADD]], %a 26 ; CHECK-NEXT: [[T3:%.*]] = fadd fast float [[REASS_MUL]], %d 27 ; CHECK-NEXT: ret float [[T3]] 28 ; 29 %t0 = fmul fast float %a, %b 30 %t1 = fmul fast float %a, %c 31 %t2 = fadd fast float %t1, %d ; a*c+d 32 %t3 = fadd fast float %t0, %t2 ; a*b+(a*c+d) 33 ret float %t3 34 } 35 36